Perceraian Nikah Sirri Dan Pengaruhnya Terhadap Hak Anak Di Pengadilan Agama Mojokerto - Dwi Nur Kasanah; Ahmad Faruq (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research analyzes the process of isbat of nikah sirri divorce and its effect on children's rights at the Mojokerto Religious Court. To investigate the isbat of nikah sirri divorce and its effect on children's rights by analyzing court decisions. Through field data collection through in-depth interviews and observation, as well as analysis of legal documents and appropriate literature. The results of this study show that the process of isbat of nikah sirri divorce involves several stages, including the submission of an isbat application, examination of witness testimony, and the judge's consideration in deciding divorce isbat. The effect of isbat of nikah sirri divorce on children's rights can include aspects such as child custody arrangements, child maintenance, and child inheritance rights. In Mojokerto Religious Court, the case of itsbat nikah before divorce is the same as in other religious courts. In fact, according to the judge of the Mojokerto Religious Court within a period of six months running in 2023. It can be concluded that the process of isbat nikah sirri divorce begins with the submission of an isbat application and ends with a judge's decision. Isbat divorce of nikah sirri affects the rights of children in the Mojokerto Religious Court.